2018
DOI: 10.1097/md.0000000000012955
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value role of radiofrequency lesion size by cardiac magnetic resonance imaging on outcomes of ablation in patients with ischemic scar-related ventricular tachycardia

Abstract: Inadequate ablation lesion formation may be responsible for post-ablation ventricular tachycardia (VT) recurrences.We aimed to evaluate whether visualisation of radiofrequency (RF) lesion size by cardiac magnetic resonance imaging (CMR) has any role in predicting adequacy of lesion and in estimating outcome.Retrospective pilot studyNine consecutive patients (8 male, age 60 ± 13 years) underwent ablation for sustained VT because of ischemic scar were evaluated for pre- and post-procedure scar tissue by CMR to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Similar acute changes on nonweighted images can be seen in animal models of both healthy and postinfarction cardiac tissue 9,12 . In human studies, LGE‐CMR imaging performed 24 h postablation can identify imaging characteristics resembling microvascular obstruction (a region of dark core surrounded by LGE enhancement in native scar tissue) in targeted areas 13 . Our group has recently demonstrated that these acute changes consistent with microvascular obstruction (DCL) persist in the chronic postablation phase and correlate well to areas of myocardial inexcitability at the time of repeat procedures 7 .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Similar acute changes on nonweighted images can be seen in animal models of both healthy and postinfarction cardiac tissue 9,12 . In human studies, LGE‐CMR imaging performed 24 h postablation can identify imaging characteristics resembling microvascular obstruction (a region of dark core surrounded by LGE enhancement in native scar tissue) in targeted areas 13 . Our group has recently demonstrated that these acute changes consistent with microvascular obstruction (DCL) persist in the chronic postablation phase and correlate well to areas of myocardial inexcitability at the time of repeat procedures 7 .…”
Section: Discussionmentioning
confidence: 68%
“…LGE-CMR imaging performed 24 h postablation can identify imaging characteristics resembling microvascular obstruction (a region of dark core surrounded by LGE enhancement in native scar tissue) in targeted areas. 13 Our group has recently demonstrated that these acute changes consistent with microvascular obstruction (DCL) persist in the chronic postablation phase and correlate well to areas of myocardial inexcitability at the time of repeat procedures. 7 The current study highlights the role of these prior ablation lesions as fixed, inexcitable barriers on a modified arrhythmogenic substrate.…”
Section: Imaging Postablationmentioning
confidence: 99%
“…Moreover, there has been evidence that the presence of MVO post-ablation is associated with a lower incidence of VT recurrence. 11 Although different wash-in kinetics of very dense scar might be a possible explanation for the persistence of MVO-like lesions, further studies and histological validation are required to unravel the underlying pathophysiology and evaluate clinical implications. 6…”
Section: Discussionmentioning
confidence: 99%
“…The practical need for MRI in patients with implantable non-MR conditional devices spans many common clinical scenarios, including assessment of the etiology of nonischemic cardiomyopathy by LGE pattern, substrate detection for ventricular arrhythmia ablation procedures, and prognostic stratification for mortality and morbidity across a spectrum of cardiomyopathies. [12][13][14][15][16][17][18][19][20] Previous studies have also illustrated that there is clinical value in the performance of MRI in patients with a range of cardiac implantable electronic devices, resulting in an altered diagnosis in up to 16% of patients and a change in management in 83% of patients. 21 The advancements made in demonstrating both general safety and clinical utility of MRI in patients with ICDs over the last several years have helped to secure its role as an important diagnostic tool, as well as garner recognition for reimbursement by payer groups.…”
Section: Discussionmentioning
confidence: 99%